Analisis Kecelakaan Kerja Di Rumah Sakit Universitas Gadjah Mada Yogyakarta - Sarastuti, Dewi; , Heru Subaris K, SKM., M.Kes; , Anisa Catur Wijayanti, S.KM.,M.Epid (2016)
Number of accidents in Gadjah Mada University Hosptal still exceeds the target of zero accident. This study aims to describe a work accident, the characteristics of respondents and jobs, environmental factors are influential, classification and losses due to accidents. This research method uses quantitative methods with descriptive analysis. Univariate analysis was conducted to determine the characteristics of respondents and jobs as well as environmental factors. The number of samples taken is total sampling as many as 23 people. The results showed that most respondents age is the age of 26-35 years (60,9%), female gender (69,6%), working time <1 year (39,1%), level of education D3 (43,5%), the nursing profession (47,8%). Occur in the morning shift (60,9%), work unit at Pharmaceutical and Sterilization Instalation (26,1%). Environmental factors most physical factors (95,7%). Most accident classification by type of injury is in contact with needles and other sharp objects (69,6%), by cause for portable work equipment (69,6%), according to the type of wounds or injuries such as superficial injuries and open wounds (78,3%), according to the location in the usual workplace (73,9%), according to the impact of the injury no working days lost (78,3%), according to the type of work in the form of medical action (73,9%), according to a deviation from the normal state in the form of lack of control at work tool (73,9%), according to the location of the injured body part on fingers (82,6%). Losses incurred amounting to Rp 11.103.014 and 46 working days lost.